Shifting goal posts: the impact of academic workforce reshaping and the introduction of teaching academic roles on the Scholarship of Teaching and Learning - Flavell, Helen; Roberts, Lynne; Fyfe, Georgina; Broughton, Michelle (Australian Association for Research in Education, 2017)
This qualitative study reports on findings from interviews with ten academics in an Australian university six to twelve months following academic workforce reshaping and the widespread introduction of teaching academic roles. The research aimed to determine how the workforce reshaping impacted on the capacity of academics with teaching responsibilities to engage in the Scholarship of Teaching and Learning (SoTL). Findings indicate that whilst academics were willing to undertake SoTL, participants’ capacity to engage was hampered by the workload model, middle academic leaders’ capacity to define and lead SoTL, and a perceived lack of SoTL value. A major concern for participants was that shifting goal posts (in relation to roles and expectations) would make it difficult to successfully apply for future academic work. The research indicates the need for the sector to consider the selection criteria for middle leadership roles, as well as ongoing academic leadership development to support adaptability and change agility.